Design for high energy storage density and temperature-insensitive lead-free antiferroelectric ceramics. Issue 17 (22nd February 2019) - Luo, Nengneng; Han, Kai; Zhuo, Fangping; Liu, Laijun; Chen, Xiyong; Peng, Biaolin; Wang, Xinpeng; Feng, Qin; Wei, Yuezhou
Abstract : High energy density was achieved by designing a AgNbO3 based lead-free system. Abstract : Dielectric capacitors with high power density and excellent temperature stability are highly demanded in pulsed power systems. AgNbO3 -based lead-free antiferroelectric ceramics have been proven to be a promising candidate for energy storage applications. Nevertheless, the recoverable energy storage density ( W rec ) still needs to be further improved to meet the requirements of the miniaturization and integration of pulsed power systems. In order to significantly increase W rec, a strategy, by introducing A-site vacancies, stabilizing antiferroelectricity and decreasing the grain size, is proposed in this work. Here, Ag1−2 x Ca x NbO3 solid solutions were designed for achieving high maximum polarization ( P max ), large antiferroelectric–ferroelectric electric field ( E F ) and high breakdown electric field ( E b ). A high P max of 39.6 μC cm −2, a large E F of 179 kV cm −1 and an E b of 220 kV cm −1 were achieved in Ag0.92 Ca0.04 NbO3 ceramics, leading to an ultrahigh W rec of 3.55 J cm −3 . The significantly improved W rec is about 2 times as high as that of the pure AgNbO3 counterpart. Meanwhile, the Ag0.92 Ca0.04 NbO3 ceramics exhibited temperature-insensitive W rec with minimal variation less than 1.5% from room temperature up to 100 °C. A Ginzburg–Landau–Devonshire (GLD) phenomenology was proposed to reveal the increased stability of antiferroelectricity and the temperature-insensitive W rec, which suggested that they are closely associated with the tailoring of free energy barriers for antiferroelectric–ferroelectric phase transition. The excellent energy storage performance makes the Ag1−2 x Ca x NbO3 system a good candidate for advanced pulsed power capacitors. More importantly, our findings open a new way for developing high performance AgNbO3 -based and other lead-free systems for energy storage.